Analisis Kinerja Plant Produksi PT. JCC Dengan Menggunakan Perhitungan Overall Equipment Evectiveness (OEE) - Khaerul Fahmi; Setiawan; Wanto; Wikrama Wardana (LPPM Universitas Pramita Indonesia, 2022)
PT. JCC Established in April 1973, PT Jembo Cable Company Tbk. started by producing Low Voltage Electrical Cables - copper conductors. Then continue to add product varieties, such as Low Voltage Cable - aluminum conductor, Medium Voltage Cable, Telephone Cable and Fiber Optic Cable and also expand its market. Production Plant performance can be improved or maintained by conducting regular evaluations of the process. The evaluation carried out is by analyzing OEE (Overall Equipment Effectiveness). OEE (Overall Equipment Effectiveness) is a calculation method used to determine the effectiveness of a process that is being implemented by identifying the percentage of production time that is truly productive which is influenced by three factors, namely availability, performance, and quality. reached 85% or above. The research was conducted by observing the cable production process at the Aluminum Cable Plant and the Copper Cable Plant. Based on the observations made from January 2021 to June 2021, the highest OEE value was obtained for the Aluminum Cable Plant in January and February, namely 97% and 94% while for the next month below 90%. For the Copper Cable Plant, since observing from January 2021 to June 2021, it has not yet reached the required OEE value, which is 85% and above. From the results of the analysis, the main factor is not achieving the OEE Value influenced by the low availability ratio It's because almost 50% of the machines in the Aluminum Cable Plant and 25% of the machines in the Copper Cable Plant don't get a workload.